Activation of protein kinase C inhibits signaling by members of the insulin receptor family. - Danielsen, A.G.; Liu, F.; Hosomi, Y.; Shii, K.; Roth, R.A. (Journal of Biological Chemistry, 1995)
Stimulation of the activity of protein kinase C by pretreatment of cells with phorbol esters was tested for its ability to inhibit signaling by four members of the insulin receptor family, including the human insulin and insulin-like growth factor-I receptors, the human insulin receptor-related receptor, and the Drosophila insulin receptor. Activation of overexpressed protein kinase C alpha resulted in a subsequent inhibition of the ligand-stimulated increase in antiphosphotyrosine-precipitable phosphatidylinositol 3-kinase mediated by the kinase domains of all four receptors. This inhibition varied from 97% for the insulin receptor-related receptor to 65% for the Drosophila insulin receptor. In addition, the activation of protein kinase C alpha inhibited the in situ ligand-stimulated increase in tyrosine phosphorylation of the GTPase-activating protein-associated p60 protein as well as Shc mediated by these receptors. The mechanism for this inhibition was further studied in the case of the insulin-like growth factor-I receptor. Although the in situ phosphorylation of insulin-receptor substrate-1 and p60 by this receptor was inhibited by prior stimulation of protein kinase C alpha, the in vitro tyrosine phosphorylation of these two substrates by this receptor was not decreased by prior stimulation of the protein kinase C alpha in the cells that served as a source of the substrates. Finally, the insulin-like growth factor-I-stimulated increase in cell proliferation was found to be inhibited by prior activation of protein kinase C alpha.(ABSTRACT TRUNCATED AT 250 WORDS)